2019
DOI: 10.1111/bph.14862
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of β2‐adrenoceptors is neuroprotective in the LPS inflammatory rat model of Parkinson's disease

Abstract: Background and Purpose: Chronic inflammation may play a role in the pathogenesis of Parkinson's disease (PD). Noradrenaline is an endogenous neurotransmitter with anti-inflammatory properties. In the present investigation, we assessed the immunomodulatory and neuroprotective efficacy of pharmacologically targeting the CNS noradrenergic system in a rat model of PD.Experimental Approach: The impact of treatment with the β 2 -adrenoceptor agonists clenbuterol and formoterol was assessed in the intranigral LPS rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 55 publications
0
17
1
Order By: Relevance
“…By contrast, a β2AR antagonist, propranolol, increased the acetylation of H3k27 [ 12 ]. In a lipopolysaccharide (LPS) inflammatory PD rat model, β2AR stimulation reduced the motor deficits following intranigral LPS injection and decreased the loss of dopaminergic neuron and LPS-induced microgliosis in substantia nigra [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, a β2AR antagonist, propranolol, increased the acetylation of H3k27 [ 12 ]. In a lipopolysaccharide (LPS) inflammatory PD rat model, β2AR stimulation reduced the motor deficits following intranigral LPS injection and decreased the loss of dopaminergic neuron and LPS-induced microgliosis in substantia nigra [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that a β 2 -selective agonist terbutaline but not a β 1 -selective agonist restrains the microglial proliferation via enhancing intracellular cAMP level ( Fujita et al, 1998 ). A number of studies reported that β 2 -adrenergic receptors inhibit microglia-mediated neuroinflammation via multiple signaling pathways to protect DA neurons from damage ( Qian et al, 2009 , 2011 ; Peterson et al, 2014 ; O’Neill et al, 2020 ). One of the studies showed that transformation from an M1- to M2-like phenotype in LPS-activated microglia by β 2 -adrenergic receptors agonists involves activation of the classical cAMP/PKA/CREB as well as the PI3K and p38 MAPK signaling pathways ( Sharma et al, 2019 ).…”
Section: Role Of Adrenergic Receptors In Microglial Activation Of Parkinson’s Diseasementioning
confidence: 99%
“…Another study reported that low doses of salmeterol inhibit microglial activation through a β 2 AR/β-arrestin2-dependent but cAMP/protein kinase A-independent pathway ( Qian et al, 2011 ). A recent study indicated that β 2 -adrenergic receptors activation using different agonists dramatically alleviates the progression of dopaminergic neurodegeneration via inhibiting microglial activation in the LPS-challenged inflammatory PD mouse model ( O’Neill et al, 2020 ).…”
Section: Role Of Adrenergic Receptors In Microglial Activation Of Parkinson’s Diseasementioning
confidence: 99%
“…The For the statistical analysis, IBM SPSS V22 software was used, to find the correlation and coefficient using the mean, standard deviation, standard error, degree factors, significance was analysed by performing ANOVA descriptive analysis [49,50]]. To find the significance and relationship between groups, Turkey Honest Significance Difference (HSD) Post Hoc test was performed.…”
Section: 4classificationmentioning
confidence: 99%
“…To find the significance and relationship between groups, Turkey Honest Significance Difference (HSD) Post Hoc test was performed. In our statistical analysis, the sample size was calculated using GPower 3.1 software [49]. The total sample size of 93 was taken divided into 3 groups such as SMOTE 31 samples, NEAR MISS 31 samples and IMBALANCE 31 samples were used.…”
Section: 4classificationmentioning
confidence: 99%